PENINGKATAN KEMAMPUAN MENENTUKAN KELIPATAN PERSEKUTUAN TERKECIL MELALUI BERTUKAR PASANGAN - diah wahaneni (Program Pascasarjana Universitas Islam Darul `Ulum Lamongan, 2017)
The aim of this study was to describe the increase of the ability in determining the least common multiple via pair exchange in the sixth graders of the state elementary school Plosoboden, Deket. The research was conducted in the form of classroom action research (PTK), which consisted of two cycles, each cycle consisting of four phases, namely planning (plan), action (action), observation (observation), and reflection (reflection). Based on the results of data analysis, it showed that the administration of a couple exchanging method can improve the ability of determining the least common multiple. This was evidenced in the first cycle the average value of the class, originally 62.85% increased to 74.64% and cycle II class average value increased to 91.07%. Thus, the application of a pair exchange method was able to improve the ability of determining the least common multiple.